"THE RELATIONSHIP BETWEEN ANGLES OF EYE DEVIATION WITH THOSE OF FACE TURN IN DUANE’S RETRACTION SYNDROME TYPE I" - I. Ahadzadegan R. Amiri (Acta Medica Iranica, 2004)
Duane’s retraction syndrome (DRS) type I is often associated with esotropia (ET) and face turn in those with fusion. This study was designed to delineate the quantitative relationship between the angles of eye deviation with that of face turn. Ten patients with DRS type I with ET and face turn toward the deviated eye, who had central fixation, were chosen. Esodeviation was measured by alternate prism-cover test, and the angle of face turn was measured by an orthopedic protractor in degree and then converted to prism diopter. The subtraction of eye deviation from face turn showed 2.4 prism diopters of face turn underestimation in comparison with esodevition, which is so small that deviations of eye and face may be considered virtually equal.